The Antimicrobial Susceptibility of Porphyromonas gingivalis: Genetic Repertoire, Global Phenotype, and Review of the Literature - Georg Conrads; Tim Klomp; Dongmei Deng; Johannes-Simon Wenzler; Andreas Braun; Mohamed M. H. Abdelbary (MDPI AG, 2021)
The in vitro antimicrobial susceptibility of 29 strains of the major periodontal pathogen Porphyromonas gingivalis and three P. gulae (as an ancestor) to nine antibiotics (amoxicillin, amoxicillin/clavulanate, clindamycin, metronidazole, moxifloxacin, doxycycline, azithromycin, imipenem, and cefoxitin) was evaluated by E-testing of minimal inhibitory concentration (MIC) according to international standards. The results were compared with 16 international studies reporting MICs from 1993 until recently. In addition, 77 currently available P. gingivalis genomes were screened for antimicrobial resistance genes. E-testing revealed a 100% sensitivity of P. gingivalis and P. gulae to all antibiotics. This was independent of the isolation year (1970 until 2021) or region, including rural areas in Indonesia and Africa. Regarding studies worldwide (675 strains), several method varieties regarding medium, McFarland inoculation standards (0.5-2) and incubation time (48-168 h) were used for MIC-testing. Overall, no resistances have been reported for amoxicillin + clavulanate, cefoxitin, and imipenem. Few strains showed intermediate susceptibility or resistance to amoxicillin and metronidazole, with the latter needing both confirmation and attention. The only antibiotics which might fail in the treatment of P. gingivalis-associated mixed anaerobic infections are clindamycin, macrolides, and tetracyclines, corresponding to the resistance genes erm(B), erm(F), and tet(Q) detected in our study here, as well as fluoroquinolones. Periodical antibiotic susceptibility testing is necessary to determine the efficacy of antimicrobial agents and to optimize antibiotic stewardship.